Indians in Apartheid South Africa: class, compromise and controversy in the era of the Group Areas Act, 1952–1962. Issue 1 (2nd January 2021) - Yengde, Suraj
ABSTRACT: This paper looks at the implementation of the notorious Group Areas Act between 1952 and 1962, and the struggle of the Transvaal Indian community in responding to the Act. Since the Group Areas Act threatened the very existence of the Indian community in South Africa, two major Indian bodies – Natal Indian Congress (NIC) and Transvaal Indian Congress (TIC) – played a pivotal role in promoting regional awareness of the Act by organizing important conferences protesting against the Act. The Indian community came together as a unified group to narrate historical atrocities, something that was never discussed among the Indian circles before. There were incidents during the Group Areas Act protest when the Indian community leadership was divided over ideological differences in the Transvaal region. Incidents like these suggest that the unity within the Indian leadership, which is often discussed in the South African race history, was subject to public scrutiny. Drawing upon the archival materials of Transvaal Indian Congress Mass Conference in 1962 and the private papers of prominent Indian figures such as Amina Cachalia and the collections of Hassim Seedat along with in-depth interviews with activists, merchants and residents of Fordsburg, this paper aims to provide exclusive insights into the tactics employed by the Indian organizations in mobilizing against the Act.